THE EFFECT OF STORY IMPRESSION STRATEGY AND READING MOTIVATION TOWARD THE EIGHTH GRADE STUDENTS’ READING COMPREHENSION ACHIEVEMENT AT SMP NEGERI 2 PAMPANGAN OKI - Lismania Lismania (ELTE Journal (English Languange Teaching and Education), 2019)
AbstractThis research is concerned with the effect of Story Impression Strategy and motivation towards reading comprehension achievement of the eighth grade students at SMPN 2 Pampangan OKI. The data were taken from reading test and questionnaire. The test was analyzed by using descriptive statistic, normality, homogeneity, independent simple t-test, and two way anova. Based on the data, it was found that; There was a significant difference in reading comprehension achievement between the students who have high level of motivation and those who have low reading motivation who are taught by using Story Impression strategy, there was a significant difference in reading comprehension achievement between the students who have a high reading motivation and those who have low reading motivation who are taught by using conventional strategy, there was a significant difference in students’ reading comprehension achievement taught using Story Impression strategy and conventional strategy. And the last, there was a significant interaction effect of Story Impression strategy and reading motivation toward students’ reading comprehension achievement. Conclusion suggests that Story Impression Strategy was effective for students who have high and low motivation.Keywords: Story Impression Strategy, Conventional Strategy, Reading Motivation, Reading Comprehension Achievement